2022
DOI: 10.1021/acsaelm.2c00063
|View full text |Cite
|
Sign up to set email alerts
|

High-Endurance Ferroelectric (La, Y) and (La, Gd) Co-Doped Hafnium Zirconate Grown by Atomic Layer Deposition

Abstract: Thin films based on stoichiometric hafnium zirconate doped and co-doped with La, Gd, and/or Y have been grown by atomic layer deposition on TiN electrodes. The resulting TiN−ferroelectric−TiN capacitors have shown high endurance up to 1 × 10 11 switching cycles. The simultaneous use of two dopants (Y, La) or (Gd, La) in hafnium zirconate increases the amount of orthorhombic and tetragonal phases. Fatigue-free capacitors with remnant polarization ≥15 μC/cm 2 at 1 × 10 11 endurance cycles have been obtained for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 71 publications
(108 reference statements)
0
8
0
Order By: Relevance
“…It was observed that the distribution coefficient of Th 4+ on the Dowex 1 × 8 resin increased with the concentration of HNO 3 , reaching a maximum value of 237.29 mL·g –1 in 9 M HNO 3 . In 9 M HNO 3 , Th 4+ predominantly exists as Th­(NO 3 ) 6 . Therefore, it can undergo a Cl – exchange with Dowex 1 × 8 anion exchange resin, resulting in its strong adsorption onto the resin. On the other hand, Ba, Y, and La remained in their cationic forms under these conditions and can be directly eluted from the Dowex 1 × 8 resin.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the distribution coefficient of Th 4+ on the Dowex 1 × 8 resin increased with the concentration of HNO 3 , reaching a maximum value of 237.29 mL·g –1 in 9 M HNO 3 . In 9 M HNO 3 , Th 4+ predominantly exists as Th­(NO 3 ) 6 . Therefore, it can undergo a Cl – exchange with Dowex 1 × 8 anion exchange resin, resulting in its strong adsorption onto the resin. On the other hand, Ba, Y, and La remained in their cationic forms under these conditions and can be directly eluted from the Dowex 1 × 8 resin.…”
Section: Resultsmentioning
confidence: 99%
“…Patrick et al 99 reported Al + Si co-doped HfO 2 with remnant polarization of ∼20 μC cm −2 and enhanced endurance up to 10 8 cycles. Mihaela et al 98 investigated La + Y/Gd co-doped HZO, and as shown in Fig. 10, the (Y, La) or (Gd, La) co-doped HZO thin films were found to increase the amount of o- and t- phases (Fig.…”
Section: Defect-modulated Ferroelectricitymentioning
confidence: 95%
“…Mihaela et al 98 investigated La + Y/Gd co-doped HZO, and as shown in Fig. 10, the (Y, La) or (Gd, La) co-doped HZO thin films were found to increase the amount of o-and t-phases (Fig.…”
Section: Mixed Ion Co-dopingmentioning
confidence: 95%
“…(a) Endurance and remanent polarization ( P r ) from various previous studies, as reproduced from a previous publication by Park et al References [a] to [o] are referred from refs and in the same order. Panel a was reproduced with permission from ref .…”
mentioning
confidence: 99%